Variations in presenting citations - Syed Sahil, Sharifah Azizah (Universiti Utara Malaysia, 1995)
This study is aimed at investigating the variation of styles with emphasis on citation techniques employed by expert writers. It covers the types of citations, distribution of tenses and reporting verbs used. The findings suggested that various techniques have been exploited. It implies that stylistic aspects in presenting citations have been ignored by expert writers.